Genetic Diversity and Phylogenetic Relationships of Mountain Papaya (Vasconcellea pubescens) in Dieng Plateau Based on Internal Transcribed Spacer Sequence - Muhammad Said Rifqi; Abdul Razaq Chasani (AGRIVITA Journal of Agricultural Science, 2023)
The Dieng Plateau is an area used to cultivate Mountain Papaya (Vasconcellea pubescens A.DC.) as a food commodity in Indonesia. Research on diversity and relationships is vital as a first step in Mountain Papaya conservation in the Dieng Plateau. The study aims to determine the genetic diversity and relationship between Mountain Papaya accessions using Internal Transcribed Spacer (ITS) rDNA sequences. Fourteen accessions of Mountain Papaya with different sex distributions and altitudes are amplified using ITS1 and ITS4 primers. The genetic diversity is analyzed using the DnaSP 5.10.1 program. The Maximum Likelihood (ML) approach in MEGA 11 is utilized for assessing phylogenetic tree data based on ITS-rDNA regional sequences. With high haplotype diversity (Hd) values of 1.000 ± 0.027 and high nucleotide diversity (π) values of 0.09674 ± 0.00978, Mountain Papaya exhibits a high level of genetic diversity. Three main clades were identified in the phylogram tree based on the 14 ITS-rDNA sequences of Mountain Papaya. The results of this diversity data can support breeding programs intended to boost Mountain Papaya variety production.